Key Diagnostic Features in Uroradiology A Case-Based Guide - Wang, Li-Jen.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents a wealth of images of the different diseases and conditions encountered in the field of uroradiology with the aim of enabling the reader to recognize lesions, to interpret them appropriately, and to make correct diagnoses. The images have been selected because they depict typical or classic findings and provide a route to lesion recognition that is superior to memorization of descriptions. The imaging modalities represented include CT, CT angiography, CT urography, MRI, MRA, MRU, diffusion-weighted MRI and ADC mapping, dynamic contrast-enhanced MRI, sonography, conventional angiography, excretory urography, retrograde pyelography, cystography, urethrography, and voiding cystourethrography. For each depicted case, important imaging features are highlighted and key points identified in brief accompanying descriptions.   Readers will find that the book provides excellent guidance in the selection of imaging modalities and facilitates diagnosis. It will be an ideal ready source of information on key imaging features of urinary tract diseases for medical students, residents, fellows, and physicians handling these diseases.
Normal variant and congenital anomalies.- Urinary tract infection.-  Renal cystic disease -- Renal parenchymal neoplasms.- Lesions of the renal pelvicalyceal system, ureter, bladder and urethra -- Vascular diseases -- Retroperitoneum -- Adrenal gland.- Male reproductive system: Prostate , seminal vesicles and testicular lesions.- Female reproductive system: Uterine body, uterine cervix, ovary, vagina -- Nephrological, systemic and non-urinary diseases with urinary tract involvement.
Keywords: Radiology; Urology; Nephrology; Imaging / Radiology; Urology; Nephrology